Uma análise sobre assédio sexual na UFRN - Silva, Maria Paula França da (2022)
This research aimed to highlight the ramifications of sexual harassment complaints for female servants and students at UFRN. In this context, we carried out virtual participant observation in the plenary sessions promoted by the Student Central Directory (DCE) and in discussions on the topic on the social networks Twitter and Instagram. We also conducted semi-structured interviews (via Google Meet) with two university employees, namely: i) the first, victim-complainant; ii) the second, active in the reception and guidance to victims, in addition to; iii) a member of the DCE. From the data collected, as well as from the literature (sexual harassment in the legal, university scope, such as violence and gender issues), we found that UFRN does not guarantee the reception or guidance to victims, filing complaints or continuing the process without punishing the victims. harassers. In this sense, there are student initiatives, such as the actions of the DCE (women's plenary sessions, letter to the dean, acts of in-person mobilization, rejection notes) and also of civil servants, who work to support victims. Finally, we observed that the process of elaboration and circulation of rumors discourages victims from reporting formally (although this occurs in previous initiatives, informally), for fear of the possible negative consequences they may suffer. Thus, we conclude that sexual harassment is mostly guided by women (who make up the majority of victims), demonstrating that perhaps there is a cooperativism between men who commit this harassment. As for UFRN's position, only after informal complaints on social media did the institution decide to carry out a public consultation (in September 2022) to identify cases of sexual harassment and gender violence suffered within the university.